Narratives of financial inclusion: a critical discourse analysis of microfinance campaigns in rural Indonesia - Mohammad Anis Sumadi (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Financial inclusion remains a central challenge in rural Indonesia, where microfinance campaigns are widely promoted as tools for poverty alleviation yet often carry implicit discursive and symbolic framings. Objective: The purpose of this research is to examine how empowerment is constructed in microfinance campaigns through linguistic, narrative, and visual strategies. Method: This study employed a qualitative research design integrating Critical Discourse Analysis, Narrative Analysis, and Multimodal Discourse Analysis to investigate a corpus of posters, videos, testimonials, and public statements from microfinance institutions. Results: The findings reveal that empowerment is discursively framed as a benevolent act of institutions, with slogans and public statements emphasizing collective progress while positioning citizens as dependent subjects; narrative structures predominantly follow a transformation arc, portraying hardship, intervention, and success while omitting systemic barriers; and visual-symbolic elements such as color schemes, logos, and images of women entrepreneurs reinforce institutional authority and normalize paternalistic views of empowerment. These results suggest that campaigns are effective in mobilizing participation but simultaneously constrain community agency by narrowing empowerment to institutional dependency. Implication: The implications of this study highlight the need for more participatory and reflexive approaches in financial inclusion communication that recognize rural communities as active partners rather than passive beneficiaries. Novelty: This study shows how microfinance campaigns construct empowerment through discursive, narrative, and visual strategies that mobilize participation while subtly reinforcing institutional authority and limiting community agency.